Cross-sectional transverse area and hyperintensities on magnetic resonance imaging in relation to the clinical picture in cervical spondylotic myelopathy - Kadanka, Zdenek; Kerkovsky, Milos; Bednarik, Josef; Jarkovsky, Jiri (Spine, 2007)
STUDY DESIGN: Prospective observational cohort study. OBJECTIVE: To ascertain the threshold of critical spondylotic cervical cord compression and its relation to MRI-increased signal intensities. SUMMARY OF BACKGROUND DATA: The critical degree of spinal cord compression required to induce significant clinical signs remains unknown. METHODS: The study group consisted of 243 patients (mean age, 53.9 +/- 9.8 years), with spondylotic cervical spine compression. The transverse cross-sectional area of the spinal cord at the level of maximum compression was measured, while MRI hyperintensities were recorded and related to clinical status and quantified by modified JOA score (mJOA). RESULTS: A statistically significant difference in mJOA was shown between patients with a spinal cord sectional area of under 50 mm2 and a group of patients with a spinal cord sectional area of over 60 mm2. This difference was highly significant (P = 0.001) in a subgroup with MRI hyperintensities (187 patients, P = 0.001), whereas within the group of patients without hyperintensities this difference was not observed (P = 0.63). CONCLUSION: The critical degree of spinal cord compression needed to induce clinically significant signs was found between 50 and 60 mm2 of cross-sectional transverse area at the level of maximal compression in association with MRI hyperintensities.
Keywords: komprese míchy; Male; kohortové studie; Spinal Cord; magnetická rezonanční tomografie; Cohort Studies; Spinal Osteophytosis; osteofytóza páteře; radikulopatie; Adult; Radiculopathy; Aged; dospělí; Prospective Studies; mužské pohlaví; senioři; Severity of Illness Index; Cervical Vertebrae; lidé; ženské pohlaví; mícha; Humans; krční obratle; stupeň závažnosti nemoci; Magnetic Resonance Imaging; Female; lidé středního věku; Spinal Cord Compression; Middle Aged; prospektivní studie